Strengthening Community Health Systems Through Novel eHealth Initiatives? Commencing a Realist Study of the Virtual Health Rooms in Rural Northern Sweden - Frida Jonsson; Dean B. Carson; Isabel Goicolea; Anna-Karin Hurtig (Kerman University of Medical Sciences, 2022)
BackgroundUnlike the large body of research that has examined the 'success' or 'failure' of eHealth in terms of patient and provider perceptions or cost- and clinical effectiveness, the current study teases out ways through which a novel eHealth initiative in rural northern Sweden might result in more distal or systemic beneficial outcomes. More specifically, this paper aims to explore how and under what circumstances the so-called virtual health rooms (VHRs) are expected to improve access to person-centred care and strengthen community health systems, especially for elderly residents of rural areas. MethodsThe first phase of the realist evaluation methodology was conducted, involving qualitative interviews with 8 key stakeholders working with eHealth, business development, digitalisation, and process management. Using thematic analysis and following an abductive-retroductive analytical process, an intervention-context-actor-mechanism-outcome (ICAMO) configuration was developed and elicited into an initial programme theory. ResultsThe findings indicate that a novel eHealth initiative, which provides reliable technologies in a customized facility that connects communities and providers, might improve access to person-centred care and strengthen community health systems for rural populations. This is theorized to occur if mechanisms acting at individual (such as knowledge, skills and trust) and collective (like a common vision and shared responsibilities) levels are triggered in contexts characterised by supportive societal transitions, sufficient organisational readiness and the harnessing of rural cohesiveness and creativity. ConclusionThe elicited initial programme theory describes and explains how a novel eHealth initiative in rural northern Sweden is presumed to operate and under what circumstances. Further testing, refinements and continued gradual building of theory following the realist evaluation methodology is now needed to ascertain if the 'VHRs' work as intended, for whom, in what conditions and why.